2010
DOI: 10.1258/ijsa.2008.008445
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of stigma in HIV/AIDS and other sexually transmitted infections

Abstract: This study sought to identify stigma differences between

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 7 publications
1
15
0
Order By: Relevance
“…This theory may extend to other STIs, such as syphilis, but perhaps not to the same extent as it does with HIV due to the stigma differences that exist between HIV and other STIs. One study found that three in four respondents reported that having an HIV infection would be the most detrimental to one’s reputation when compared to other STIs [21]. Therefore, vengeance (in response to a perceived wrong by another impacting oneself) may have more on an impact on disclosure intention in considering HIV infection compared to being infected with other STIs.…”
Section: Discussionmentioning
confidence: 99%
“…This theory may extend to other STIs, such as syphilis, but perhaps not to the same extent as it does with HIV due to the stigma differences that exist between HIV and other STIs. One study found that three in four respondents reported that having an HIV infection would be the most detrimental to one’s reputation when compared to other STIs [21]. Therefore, vengeance (in response to a perceived wrong by another impacting oneself) may have more on an impact on disclosure intention in considering HIV infection compared to being infected with other STIs.…”
Section: Discussionmentioning
confidence: 99%
“…This might link to our finding that the attribution of sexual agency to women is limited to sex workers in global AIDS policy papers, which strengthens the association between HIV in women and sexually immoral behaviour. Men’s sexual agency is generally not negated, while women’s sexual agency is [89,90]. Women’s autonomy and power in sexual relations is often perceived “unfeminine” and threatening to men [23,91,92].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that STIs are stigmatizing conditions 17,19. It is also generally accepted (although not empirically proven) that GUM clinics are stigmatized through their association with STIs 20.…”
Section: Discussionmentioning
confidence: 99%